Validação de diferentes configurações numéricas para a modelagem da Baía de Todos os Santos, BTS - Monteiro, Giulian Smith Araújo (2022)
The Todos os Santos Bay is a region with high ecological and economical potential for the Bahia state and for Brazil as a whole. Because of that, there were many advances on oceanographic data sampling and on the creation of numerical models for the region in the last few years. However, the group of configurations and conditioners that best represent the Todos os Santos Bay hydrodynamics remains unknown. Four different setups were used and compared among themselves in order to define which models and settings best represent the hydrodynamic conditions from Todos os Santos Bay. Salinity, temperature, density, currents, water level and harmonic constituents’ data were used to compare the four simulations and validate their results. The simulation without the wet and dry system was the worst between the four, signaling the need for the use of this system in the modeling of such region. The different astronomical and ocean boundary models used had similar performances, with the CFSR model working in good level and velocity simulations while the WRF model helped on the best representation of the thermo-haline field. HYCOM model was inferior compared to GLORYS/Mercator in level and velocity data and superior on the thermo-haline field representation. Taking into account the possibility of calibration, a simulation with the GLORYS/Mercator model and a hybrid employment of CFSR and WRF models could be the best setup for modelling the Todos os Santos Bay.